Air Flow Cooling Improves Anterolateral Thigh Perforator Mapping Using the FLIR ONE Thermal Camera - Illg, Claudius; Krauss, Sabrina; Rothenberger, Jens; Kolbenschlag, Jonas; Daigeler, Adrien; Schäfer, Ruth Christine (Journal of Reconstructive Microsurgery, 2021)
Background Due to the variable vascular anatomy preoperative perforator mapping facilitates anterolateral thigh (ALT) free flap harvesting. Dynamic infrared perforator imaging can assist preoperative planning by displaying hot spots that represent angiosomes. This study aims to compare previously described precooling methods to develop a standardized simplified protocol for ALT perforator planning.Methods Fifty thighs were examined with a FLIR ONE thermal camera. Four different cold challenges, including alcoholic disinfection, wet laparotomy sponge cooling, fan cooling, and cold pack application, were compared. Hot spot locations within a 250 mm × 80 mm area were compared double-blinded to perforator locations determined by Doppler ultrasonography considered as gold standard.Results The matching rate of thermographic hot spots and sonographically identified perforators was 34.9 ± 22.2%. An increased matching rate of 62.2 ± 42.2% was noted taking only favored perforators (septocutaneous course, diameter >1 mm, distance <3 cm to the center, and visible concomitant veins) into account. Precooling with a fan followed by alcoholic disinfection provided clearest thermograms and fastest results.Conclusion Thermographic imaging is a reliable method for perforator imaging. Its supplemental use to ultrasound may reduce examination time and yield additional information. Precooling by air flow or alcoholic disinfection can be easily implemented and provide the best thermograms. The matching rate of thermographic hot spots and perforators increases when taking only clinically relevant perforators into account. Thermal perforator mapping therefore reduces distraction by negligible perforators.
Keywords: thermography; FLIR; perforator mapping